Digital Immersive Environments in Art: New Anthropological Horizons - Venkova, Alina V. (Actual Problems of Theory and History of Art, 2020)
Digital immersive environments are a kind of a new anthropological register in contemporary visual culture. Artists seek to move away from the traditional formats of presenting artistic content referring to the divided channels of influence designed only for sight and hearing. Immersive practices actively develop the creation of a total immersion environment. Artists work with the body and the psychoemotional state of the recipient forming a multi-sensory artistic environment.Visual and auditive impressions are supported by tactile, kinaesthetic experience, creating a new anthropological register of total inclusion in the perception of a work of art. In itself, the creation of immersive environments is not new. At all stages of the development of the artistic language, attempts were made to develop an instrument for a comprehensive impact on all the senses of a man.This can be seen in ancient mysteries, theatrical cultic rituals, carnival culture, temple architecture, and art.The most obvious break with such syntheses is observed in the era of rationalism, when each of the arts seeks and acquires its own independent language responsible for a certain channel of perception. Active attempts to return to the total synthesis of the impact on all senses have been undertaken again with the emergence of modernism, they can be found in the era of modernity, avant-garde, and, not least, in the synesthesia practices of the German expressionists and the French theatre of cruelty. In the neo-avant-garde era, these experiments begin to be widely conducted in happening, performance and total installation. The novelty of the present moment is the emergence of digital technologies as an artistic resource and a basis for creating immersive environments. In modern art, the effect of immersion is increasingly achieved not through architectural solutions or sound and light discoveries of temple synthesis, not at the expense of the physical creation of total media as it was in the “large installations” of the 90s‑2000s, but due to a digital illusion submerging man in the ghost world of a digital biosensor environment. Immersion is achieved through digital architecture affecting all senses and actively involving the body of the viewer in the process of experiencing an artistic event. In full, these experiments are manifested in the activities of “team Lab” and “imaginarium studios UK”.
Keywords: immersive environments; digital art; total installations; happening; performance; visual culture; synaesthesia